Relationship between Pain and Serum Ferritin Levels in Adult Transfusion-Dependent Thalassemia - Shenny Dianathasari Santoso; Uni Gamayani; Asep Nugraha Hermawan; Pandji Irani Fianza; Aih Cahyani; Lisda Amalia; Yusuf Wibisono; Ramdan Panigoro (Global Medical & Health Communication, 2021)
Patients with transfusion-dependent thalassemia (TDT) may experience an increase in ferritin due to shorter erythrocyte lifespan and lysis, as well as side effects of transfusion. Increasing ferritin can cause various complications, including pain, which can develop into chronic pain and interfere with life quality. This study aims to determine the relationship between pain and serum ferritin levels in adults with TDT. This study was an analytical observational study using a cross-sectional design on adult TDT patients with pain who came to the Hemato-Oncology Clinic of Dr. Hasan Sadikin General Hospital Bandung. This research was conducted from March to June 2021. All subjects were assisted to fill out the Indonesian version of the Brief Pain Inventory Short Form (BPI-SF) questionnaire before transfusion. Ferritin levels in the last three months were obtained from medical records. If more than three months, serum ferritin levels were examined. Ferritin levels and BPI-SF scores were then correlated using the Pearson test. The study was conducted on 51 adult TDT patients with pain, and the average value of ferritin levels in research subjects is 5081±2929 g/L. There was a relationship between pain (the dimensions of pain interfere with life on the BPI-SF score) and an increase in ferritin levels (p=0.042, r=0.29). The results showed there is a relationship between pain and serum ferritin levels. Regular consumption of iron chelation tablets can reduce ferritin levels and improve the quality of life for adults with TDT.